Fenofibrate Improves Insulin Resistance and Hepatic Steatosis and Regulates the Let-7/SERCA2b Axis in High-Fat Diet-Induced Non-Alcoholic Fatty Liver Disease Mice - Zhang, Dan; Niu, Shanzhuang; Ma, Yicheng; Chen, Hang; Wen, Yu; Li, Mingke; Zhou, Bo; Deng, Yi; Shi, Chunjing; Pu, Guangyu; Yang, Meng; Wang, Xianmei; et al. (Frontiers in Pharmacology, 2022)
Fenofibrate is widely used in clinical therapy to effectively ameliorate the development of non-alcoholic fatty liver disease (NAFLD); however, the specific molecular mechanism remains largely unknown. MicroRNAs (miRNAs) are key mediators in regulating endoplasmic reticulum (ER) stress during NAFLD, and deregulation of miRNAs has been demonstrated in NAFLD pathophysiology. The present study aimed to identify whether fenofibrate could influence miRNA expression in NAFLD and investigate the specific mechanism of fenofibrate in lipid metabolism disorder-associated diseases. Here, we report that fenofibrate alleviated ER stress and increased the levels of SERCA2b, which serves as a regulator of ER stress. Furthermore, the levels of let-7 miRNA were also regulated by fenofibrate, and let-7 was found to target the 3' UTR of SERCA2b. The present data suggest that protective effects of fenofibrate against insulin resistance and suppresses excessive hepatic lipid accumulation might be related to the alteration of the let-7/SERCA2b axis and alleviation of ER stress.